Analisis Kinetika Adsorpsi Zat Warna Rhodamin B menggunakan Hidroksiapatit Hasil Kalsinasi Tulang Sapi Lombok yang Diaktivasi oleh Na2CO3 - Devy Lestiana Sembiring; Muhammad Andre; Cantika Wijaya (Pure Chemistry Research, 2025)
Water pollution caused by synthetic dyes such as Rhodamine B poses a serious environmental problem due to their high toxicity, persistence, and resistance to degradation. This study investigated the potential of hydroxyapatite (HAp) synthesized from Lombok bovine bone waste and chemically activated with sodium carbonate (Na₂CO₃) as an adsorbent for Rhodamine B removal, with particular emphasis on adsorption kinetics. Hydroxyapatite was prepared through deproteinization followed by calcination at 900 °C, and subsequently modified using Na₂CO₃ activation. The synthesized materials were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and Brunauer–Emmett–Teller (BET) surface area analysis.XRD results confirmed that the activation process did not alter the primary crystalline phase of hydroxyapatite, while a slight reduction in crystallite size was observed. FTIR analysis revealed the presence of carbonate functional groups on the activated HAp surface. BET analysis showed a significant increase in specific surface area from 12.8 to 21.5 m²/g after Na₂CO₃ activation. Batch adsorption experiments demonstrated that the activated HAp achieved an equilibrium adsorption capacity of 9.87 mg/g with an equilibrium time of approximately 90 min. Kinetic analysis indicated that the adsorption process followed the pseudo-second-order model with a high coefficient of determination (R² = 0.996), suggesting that chemisorption was the dominant rate-controlling mechanism. These findings highlight the potential of Na₂CO₃-activated hydroxyapatite derived from bovine bone waste as a sustainable and effective adsorbent for dye-contaminated wastewater treatment.